Intravenous ketamine for depression: A clinical discussion reconsidering best practices in acute hypertension management - Yip, Ryan; Swainson, Jennifer; Khullar, Atul; McIntyre, Roger S.; Skoblenick, Kevin (Frontiers in Psychiatry, 2022)
Ketamine is a versatile medication with an emerging role for the treatment of numerous psychiatric conditions, including treatment resistant depression. Current psychiatry guidelines for its intravenous administration to treat depression recommend regular blood pressure monitoring and an aggressive approach to potential transient hypertensive episodes induced by ketamine infusions. While this approach is aimed at ensuring patient safety, it should be updated to align with best practice guidelines in the management of hypertension. This review defines and summarizes the currently recommended approach to the hypertensive emergency, the asymptomatic hypertensive urgency, and discusses their relevance to intravenous ketamine therapy. With an updated protocol informed by these best practice guidelines, ketamine treatment for depression may be more accessible to facilitate psychiatric treatment.